The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1136/annrheumdis-2012-eular.1146
|View full text |Cite
|
Sign up to set email alerts
|

AB1148 Diagnosis of malignancies in children with musculoskeletal complaints

Abstract: Background Musculoskeletal pain is a frequent complaint in pediatrics in both tertiary and primary care. Although musculoskeletal symptoms are not usually related to severe disease, they can represent the first manifestation of an occult malignancy. When these complaints predominate in the clinical presentation, they lead the diagnosis towards nonmalignant conditions, that are most common cause of such symptoms in children, like injuries, nonspecific reactive arthritis or inflammatory connective tissue disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Though, considering the whole spectrum of childhood cancers, musculoskeletal symptoms at debut have been found in up to 25% and musculoskeletal diagnoses in 7-12% [19][20][21]. Musculoskeletal misdiagnoses have primarily been described in children with leukemia and lymphomas [19,22], and only a few cases of musculoskeletal misdiagnoses in children with brain tumors have been described [21,23,24]. A recently published nationwide registry-based cohort study by our group, including all children with cancer in Denmark over 23 years, identified a musculoskeletal diagnosis prior to the diagnosis of cancer in 4% (33/931) with brain tumors, [20].…”
Section: Introductionmentioning
confidence: 99%
“…Though, considering the whole spectrum of childhood cancers, musculoskeletal symptoms at debut have been found in up to 25% and musculoskeletal diagnoses in 7-12% [19][20][21]. Musculoskeletal misdiagnoses have primarily been described in children with leukemia and lymphomas [19,22], and only a few cases of musculoskeletal misdiagnoses in children with brain tumors have been described [21,23,24]. A recently published nationwide registry-based cohort study by our group, including all children with cancer in Denmark over 23 years, identified a musculoskeletal diagnosis prior to the diagnosis of cancer in 4% (33/931) with brain tumors, [20].…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal misdiagnoses have primarily been described in children with leukemia and lymphomas, (18,21), and only a few cases of musculoskeletal misdiagnoses in children with brain tumors have been described. (20,22,23). A recently published nationwide registry-based cohort study by our group, including all children with cancer in Denmark over 23 years, identified a musculoskeletal diagnosis prior to the diagnosis of cancer in 4% (33/931) with brain tumors, (19).…”
Section: Introductionmentioning
confidence: 99%